Hybrid Quantum-Classical Computing: Benchmarking Algorithm Performance on Near-Term Quantum Processors for Optimization Problems - Nursahira, Alvira; Safitri, Reni; Alvin, Muhammad; BR Sitepu, Mispa Arnetty; Sembiring, David Jumpa Malem; BR Ginting, Devita Permata Sari (SEAN Institute, 2025)
This paper presents a qualitative analysis of hybrid quantum-classical computing approaches aimed at solving complex optimization problems using near-term quantum processors. Hybrid algorithms leverage the strengths of quantum and classical computing to tackle computationally intensive tasks often constrained by current quantum hardware limitations. Through an extensive literature review and synthesis of recent empirical studies, we benchmark various hybrid algorithms, such as the Quantum Approximate Optimization Algorithm (QAOA) and Variational Quantum Eigensolver (VQE), focusing on their performance, scalability, and practical applicability on noisy intermediate-scale quantum (NISQ) devices. The study highlights the advantages, challenges, and future prospects of integrating hybrid quantum-classical computation in optimization domains, providing a comprehensive framework and qualitative insights into benchmarking methodologies and critical performance metrics.